Negative electrode sheet for sulfide all-solid-state battery, method for manufacturing same, and all-solid-state battery

CN123017988APending Publication Date: 2026-10-30SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611507708.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0009]本发明提供一种硫化物全固态电池的负极极片及其制备方法、全固态电池,旨在通过双层涂布结构设计,分别解决集流体/电解质界面腐蚀问题和复合负极内部的界面稳定性问题

Benefits of technology

(1)本发明提供的硫化物全固态电池的负极极片,能够阻断集流体/电解质界面副反应,通过在集流体与硫化物-硅碳复合负极层之间设置第一涂层,该涂层仅具有电子导电性而几乎不具有离子导电性,在物理隔离的基础上,进一步从离子传输层面彻底阻断了硫化物电解质中S²-、Cl-等阴离子与铜集流体的化学交互,有效抑制了Cu2S的生成和硫化物的分解。经实验验证,采用本发明的负极极片组装的全固态电池,界面阻抗在循环过程中的增长幅度较未涂覆碳层的对比电池降低明显。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of solid-state batteries, in particular to a sulfide full-solid-state battery negative electrode sheet, a preparation method thereof and a full-solid-state battery. The sulfide full-solid-state battery negative electrode sheet comprises a current collector and a first coating layer and a second coating layer arranged on the surface of the current collector in sequence; the first coating layer is an electron-conducting and ion-insulating coating layer; and the second coating layer comprises a sulfide solid-state electrolyte and a silicon-carbon composite negative electrode material. The present application sets an electron-conducting and ion-insulating coating layer, effectively blocks the direct contact and ion exchange between the sulfide electrolyte and the copper current collector, and inhibits the interface side reaction and copper corrosion; meanwhile, the form of the carbon material in the composite negative electrode layer is regulated, and the catalytic decomposition of the sulfide on the carbon surface is reduced. The present application significantly reduces the negative electrode side interface impedance, and improves the cycle stability and coulomb efficiency of the full-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, and more specifically, to the negative electrode sheet of a sulfide all-solid-state battery and its preparation method, and the all-solid-state battery itself. Background Technology

[0002] All-solid-state sulfide batteries (ASSBs) are characterized by their high ionic conductivity (up to 10⁻⁶ ions / ... - With its high efficiency (² S / cm) and excellent machinability, sulfide all-solid-state batteries are widely considered a core technology for next-generation high-energy-density batteries. However, the commercialization of sulfide all-solid-state batteries still faces many challenges, among which the interfacial incompatibility between the current collector on the negative electrode side and the sulfide electrolyte is particularly prominent.

[0003] Studies have shown that there is intrinsic chemical incompatibility between copper current collectors and sulfide solid electrolytes, especially sulfide-germanium ore electrolytes such as Li6PS5Cl. Even under strictly anhydrous and oxygen-free inert conditions, contact between copper and sulfide electrolytes spontaneously triggers a redox reaction, leading to pitting corrosion on the copper surface, the formation of highly resistive Cu2S, and inducing the decomposition of the sulfide electrolyte. This interfacial degradation causes a sharp increase in charge transfer impedance, from approximately 300Ω to over 1000Ω, accelerating irreversible lithium loss and ultimately resulting in rapid capacity decay and premature battery failure.

[0004] Furthermore, sulfide electrolytes are extremely sensitive to humidity; even trace amounts of moisture can induce hydrolysis and release H2S gas, which further reacts with copper to form Cu2S. Even in strictly controlled dry environments, the intrinsic incompatibility between copper and sulfide electrolytes persists.

[0005] To address the aforementioned problems, existing technologies have proposed methods for applying a protective layer to the surface of copper current collectors. For example, some studies have used carbon coatings as a physical barrier for copper current collectors, which can inhibit sulfidation reactions to some extent. However, existing solutions still have the following shortcomings: First, existing carbon coatings or undercoats only serve as purely physical barriers, and their ion-blocking function has not been fully recognized and utilized. In fact, if the coating only possesses electronic conductivity and lacks ionic insulation, it cannot completely block anions (such as S²⁺) in sulfide electrolytes. - Cl - The chemical interaction between copper current collectors and other materials still carries the risk of interfacial side reactions.

[0006] Second, in the existing negative electrode active layer, catalytic side reactions can occur between the sulfide electrolyte and the carbon material under certain conditions, accelerating the decomposition of the electrolyte.

[0007] Third, existing technologies lack a systematic design for functional synergy between the current collector protective layer and the negative electrode active layer.

[0008] In view of this, the present invention is hereby proposed. Summary of the Invention

[0009] This invention provides a negative electrode sheet for a sulfide all-solid-state battery and its preparation method, as well as an all-solid-state battery. The aim is to solve the corrosion problem at the current collector / electrolyte interface and the interface stability problem inside the composite negative electrode through a double-layer coating structure design.

[0010] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: A negative electrode sheet for a sulfide all-solid-state battery includes: a current collector and a first coating and a second coating sequentially disposed on the surface of the current collector; The first coating is an electronically conductive and ionically insulating coating. The second coating comprises: a sulfide solid electrolyte and a silicon-carbon composite anode material.

[0011] Preferably, the electronic conductivity of the first coating is ≥10. -2 S / cm, ionic conductivity ≤10 -9 S / cm.

[0012] Preferably, the first coating comprises: a conductive carbon material and a binder in a mass ratio of 50~99:1~50.

[0013] Preferably, the thickness of the first coating is 1~20μm.

[0014] Preferably, the conductive carbon material includes at least one of carbon black, conductive graphite, carbon nanotubes, or graphene.

[0015] Preferably, the adhesive comprises at least one of polyvinylidene fluoride, polyacrylic acid, and styrene-butadiene rubber.

[0016] Preferably, in the second coating, the mass ratio of the sulfide solid electrolyte to the silicon-carbon composite anode material is 10~40:60~90.

[0017] Preferably, the silicon-carbon composite anode material comprises: a porous carbon framework and silicon particles loaded in the porous carbon framework.

[0018] Preferably, the specific surface area of ​​the porous carbon framework is ≤200m². 2 / g.

[0019] A method for preparing the negative electrode sheet of the sulfide all-solid-state battery, comprising the following steps: (a) After coating the first slurry onto the surface of the current collector, a first drying process is performed to form a first coating; (b) After applying the second slurry to the surface of the first coating, a second drying process and a roll pressing process are performed to form a second coating; The second slurry includes: a sulfide solid electrolyte and a silicon-carbon composite anode material.

[0020] Preferably, the solvent of the second slurry includes: a non-polar organic solvent or a weakly polar organic solvent.

[0021] Preferably, the solvent of the second slurry has a dielectric constant ≤10 and does not contain hydroxyl or amino groups.

[0022] Preferably, the pressure of the roller pressing process is 50~500MPa.

[0023] An all-solid-state battery, comprising the negative electrode of the sulfide all-solid-state battery.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The negative electrode of the sulfide all-solid-state battery provided by the present invention can block the side reaction at the current collector / electrolyte interface. By setting a first coating between the current collector and the sulfide-silicon-carbon composite negative electrode layer, the coating has only electronic conductivity and almost no ionic conductivity. On the basis of physical isolation, it further completely blocks the S² in the sulfide electrolyte from the ion transport level. - Cl - The chemical interaction between the anions and the copper current collector effectively suppresses the formation of Cu2S and the decomposition of sulfides. Experimental verification shows that the all-solid-state battery assembled using the negative electrode sheet of this invention exhibits a significantly lower increase in interfacial impedance during cycling compared to the control battery without a carbon coating.

[0025] (2) The negative electrode of the sulfide all-solid-state battery provided by the present invention has the dual functions of electronic conductivity and ion insulation. The conductive carbon material in the first coating forms a continuous electronic conductivity network, which can uniformly disperse the current density and suppress the growth of lithium dendrites caused by local overpotential. At the same time, its dense carbon layer structure acts as a physical barrier, effectively isolating the direct contact between the sulfide electrolyte and the metal current collector, preventing the latter from being corroded. The binder in the first coating fully fills the pores inside the carbon layer structure after drying, ensuring that the first coating maintains durable and reliable ion insulation. The synergistic effect of the above multiple functions fundamentally improves the stability of the negative electrode side interface.

[0026] (3) The negative electrode of the sulfide all-solid-state battery provided by the present invention solves the problem of interface stability inside the composite negative electrode. By controlling the morphology of the carbon material in the second coating, using a porous carbon skeleton with low specific surface area and uniform dispersion of sulfide electrolyte, the contact interface between sulfide and carbon material is controlled within a reasonable range, which maintains the necessary electronic conductivity network and minimizes the catalytic decomposition reaction of sulfide on the carbon surface.

[0027] (4) The method for preparing the negative electrode of the sulfide all-solid-state battery provided by the present invention has strong process compatibility. It can be achieved by conventional coating process without introducing additional complex processes such as electroplating and vapor deposition. It is highly compatible with existing lithium-ion battery electrode preparation production lines and has good industrialization prospects. Detailed Implementation

[0028] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0029] One aspect of the present invention relates to a negative electrode sheet of a sulfide all-solid-state battery, comprising: a current collector and a first coating and a second coating sequentially disposed on the surface of the current collector; The first coating is an electronically conductive and ionically insulating coating. The second coating comprises: a sulfide solid electrolyte and a silicon-carbon composite anode material.

[0030] The negative electrode of the sulfide all-solid-state battery described above can block side reactions at the current collector / electrolyte interface. By setting a first coating between the current collector and the sulfide-silicon-carbon composite negative electrode layer, this coating has only electronic conductivity and almost no ionic conductivity. On the basis of physical isolation, it further completely blocks S² in the sulfide electrolyte from the ion transport level. - Cl - The chemical interaction between the anions and the copper current collector effectively suppresses the formation of Cu2S and the decomposition of sulfides. Experimental verification shows that the all-solid-state battery assembled using the negative electrode sheet of this invention exhibits a significantly lower increase in interfacial impedance during cycling compared to the control battery without a carbon coating.

[0031] The negative electrode of the aforementioned sulfide all-solid-state battery combines electronic conductivity and ionic insulation. The conductive carbon material in the first coating forms a continuous electronic conductivity network, which can uniformly distribute the current density and suppress lithium dendrite growth caused by local overpotential. Simultaneously, its dense carbon layer structure acts as a physical barrier, effectively isolating the sulfide electrolyte from direct contact with the metal current collector and preventing corrosion of the latter. The binder in the first coating, after drying, fully fills the pores within the carbon layer structure, ensuring that the first coating maintains durable and reliable ionic insulation. The synergistic effect of these multiple functions fundamentally improves the stability of the negative electrode interface.

[0032] The negative electrode of the sulfide all-solid-state battery solves the problem of interface stability inside the composite negative electrode. By controlling the morphology of the carbon material in the second coating, using a porous carbon skeleton with low specific surface area and uniform dispersion of sulfide electrolyte, the contact interface between sulfide and carbon material is controlled within a reasonable range, which maintains the necessary electronic conductivity network and minimizes the catalytic decomposition reaction of sulfide on the carbon surface.

[0033] Furthermore, the electronic conductivity of the first coating is ≥10. -2 S / cm (e.g., can be, but is not limited to, 10) -2 S / cm, 10 -1 S / cm, 10S / cm, 10 2 S / cm, 10 3 S / cm, 10 4 S / cm or 10 5 (A point value of any one of the S / cm or a range between the two), ionic conductivity ≤10 -9 S / cm (e.g., can be, but is not limited to, 10) -9 S / cm, 10 -10 S / cm, 10 -11 S / cm or 10 -12 (A point value of either S / cm or a range between the two). High electronic conductivity ensures that the first coating has excellent electronic transport capabilities, enabling it to uniformly distribute current density and suppress local overpotentials; extremely low ionic conductivity endows it with ionic insulation properties.

[0034] Further, the first coating comprises: conductive carbon material and a binder in a mass ratio of 50~99:1~50 (e.g., but not limited to 50:50, 55:45, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5, or 99:1); preferably, it comprises: conductive carbon material and a binder in a mass ratio of 60~98:2~40. The conductive carbon material constructs a continuous electronic conductive network, and the binder, after drying, fully fills the pores inside the carbon layer, ensuring that the first coating maintains durable and reliable ionic insulation. When the proportion of conductive carbon material is too low, the conductive carbon material cannot form a connected conductive network, resulting in insufficient electronic conductivity of the coating and weakened current distribution uniformity. When the proportion is too high, the first coating loses its ionic insulation function and cannot block anions (such as S²) in the sulfide electrolyte. - Cl - The migration of substances (such as copper current collectors) to the surface of the copper current collector makes it impossible to achieve the core invention objective of suppressing interfacial side reactions and copper corrosion.

[0035] Further, the thickness of the first coating is 1~20μm (for example, it can be any one of 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 15μm, 18μm or 20μm or a range between any two), preferably 2~10μm, more preferably 3~6μm. If the first coating is too thin, it is difficult for the coating to form a continuous and dense barrier layer, and it cannot achieve physical isolation and ion insulation functions; if it is too thick, it will increase the internal resistance of the battery and the thickness of the electrode, reduce the energy density, and there is a risk of cracking and peeling of the coating.

[0036] Further, the conductive carbon material includes at least one of carbon black, conductive graphite, carbon nanotubes, or graphene. In some specific embodiments, the conductive carbon material is any one of the above-mentioned conductive carbon materials; or, the conductive carbon material is any two of the above-mentioned conductive carbon materials; or, the conductive carbon material is any three of the above-mentioned conductive carbon materials; or, the conductive carbon material is all of the above-mentioned conductive carbon materials. When multiple conductive carbon materials are used, they can be combined in any proportion.

[0037] Further, the adhesive includes at least one of polyvinylidene fluoride, polyacrylic acid, or styrene-butadiene rubber. In some specific embodiments, the adhesive is any one of the above adhesives; or, the adhesive is any two of the above adhesives; or, the adhesive is all of the above adhesives. When multiple adhesives are used, they can be combined in any proportion.

[0038] Furthermore, in the second coating, the mass ratio of the sulfide solid electrolyte to the silicon-carbon composite anode material is 10-40:60-90, including but not limited to 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, or 40:60. This ratio ensures sufficient and continuous lithium-ion transport channels around the silicon-carbon particles while preventing excessive sulfide electrolyte from accumulating on the outer surface of the carbon skeleton, thus ensuring good electrochemical performance of the anode.

[0039] Furthermore, the second coating also includes a second adhesive; the second adhesive includes at least one of chloroprene rubber (CR), polyvinylidene fluoride, polyacrylic acid, polymethacrylic acid, styrene-butadiene rubber, or polyacrylonitrile.

[0040] Furthermore, the mass ratio of the second binder to the sum of the sulfide solid electrolyte and the silicon-carbon composite negative electrode material is 1 to 10:100, including but not limited to 1:100, 3:100, 5:100, 7:100, 9:100 or 10:100.

[0041] Further, the thickness of the second coating is 20~150μm, including but not limited to point values ​​or ranges between any one of 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm or 150μm. Preferably, the thickness of the second coating is 60~70μm.

[0042] Furthermore, the sulfide solid electrolyte includes, but is not limited to, at least one of: Li6PS5Cl, Li6PS5Br, Li6PS5I, or Li3PS4. Conventional sulfide solid electrolytes in the art can be used to implement the technical solutions of this invention.

[0043] Furthermore, the silicon-carbon composite anode material includes: a porous carbon framework and silicon particles loaded in the porous carbon framework.

[0044] Furthermore, the specific surface area of ​​the porous carbon framework is ≤200m². 2 / g, including but not limited to 50m 2 / g、70m 2 / g、90m 2 / g、110m 2 / g、130m 2 / g, 150m 2 / g、170m 2 / g、190m 2 / g or 200m 2The value of any one of / g or the range between any two, preferably 100~200m 2 / g. This specific surface area, while ensuring sufficient space to accommodate silicon particles, reduces the contact reaction sites between the sulfide electrolyte and the carbon material, effectively inhibiting the catalytic decomposition of sulfides on the carbon surface and maintaining a low interfacial impedance during long-term cycling. The high specific surface area of ​​carbon materials exacerbates the catalytic decomposition of sulfide electrolytes. When the specific surface area exceeds 200 m² / g, the number of active sites on the carbon surface increases significantly, leading to irreversible decomposition of the sulfide electrolyte on the carbon surface, increased interfacial impedance, and decreased cycling performance.

[0045] Furthermore, the silicon particles loaded in the porous carbon framework account for 5% to 50% of the mass of the silicon-carbon composite anode material, including but not limited to any one of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50% or any range between two, preferably 15% to 20%.

[0046] Another aspect of the present invention relates to a method for preparing the negative electrode sheet of the aforementioned sulfide all-solid-state battery, comprising the following steps: (a) After coating the first slurry onto the surface of the current collector, a first drying process is performed to form a first coating; (b) After applying the second slurry to the surface of the first coating, a second drying process and a roll pressing process are performed to form a second coating; The second slurry includes: a sulfide solid electrolyte and a silicon-carbon composite anode material.

[0047] The method for preparing the negative electrode sheet of the sulfide all-solid-state battery has strong process compatibility. It can be achieved using conventional coating processes without introducing additional complex processes such as electroplating and vapor deposition. It is highly compatible with existing lithium-ion battery electrode sheet preparation production lines and has good industrialization prospects.

[0048] Furthermore, the first slurry includes: conductive carbon material and binder.

[0049] Furthermore, the solvent of the first slurry includes, but is not limited to, at least one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), or ethanol.

[0050] Furthermore, the solvent for the second slurry includes: a non-polar organic solvent or a weakly polar organic solvent.

[0051] Furthermore, the solvent of the second slurry has a dielectric constant ≤10 and does not contain hydroxyl or amino groups. The second slurry contains a sulfide electrolyte, which is sensitive to solvents; the aforementioned solvent can protect the sulfide electrolyte.

[0052] Furthermore, the solvent of the second slurry includes, but is not limited to, at least one of toluene, isobutyl isobutyrate, or dichloromethane.

[0053] Furthermore, the second slurry also includes a second binder.

[0054] Furthermore, the temperature of the first drying process is 60~120℃ (for example, it can be any one of 60℃, 70℃, 80℃, 90℃, 100℃, 110℃ or 120℃ or any range between two), and the time is 2~12h (for example, it can be any one of 2h, 4h, 6h, 8h, 10h or 12h or any range between two).

[0055] Furthermore, the temperature of the second drying process is 40~80℃ (for example, it can be any one of 40℃, 50℃, 60℃, 70℃ or 80℃ or any range between two), and the time is 4~24h (for example, it can be any one of 4h, 8h, 12h, 16h, 20h or 24h or any range between two).

[0056] Furthermore, the pressure of the rolling process is 50~500MPa, including but not limited to 50MPa, 100MPa, 150MPa, 200MPa, 250MPa, 300MPa, 350MPa, 400MPa, 450MPa, or 500MPa. This pressure range ensures that a tight solid-solid contact is formed between the components in the second coating, constructing a continuous and low-resistance ion / electron hybrid conduction network. Too low a pressure will result in insufficient compaction, while too high a pressure will crush the material particles.

[0057] Another aspect of the present invention relates to an all-solid-state battery, comprising the negative electrode of the sulfide all-solid-state battery described above.

[0058] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0059] Example 1 This embodiment provides a negative electrode sheet for a sulfide all-solid-state battery, the preparation method of which includes the following steps: S1. Disperse 98g of carbon black (Super P) and 2g of polyvinylidene fluoride (PVDF) in 100mL of N-methylpyrrolidone (NMP) and magnetically stir at 500rpm for 6 hours at room temperature to form a uniform first slurry.

[0060] S2. The obtained first slurry is applied to the surface of an 8μm thick electrolytic copper foil using a doctor blade coating method. The doctor blade gap is set to 30μm, and the coating speed is 3m / min. The coated copper foil is then transferred to a vacuum oven and dried at 80℃ and -0.095MPa vacuum for 4 hours to form a first coating layer (carbon coating layer) with a thickness of 6μm.

[0061] S3. In an argon glove box (O2<0.1 ppm, H2O<0.1 ppm), 30g of Li6PS5Cl powder (average particle size D50=2μm), 70g of silicon-carbon composite anode material (silicon content 20wt%, porous carbon skeleton specific surface area 150 m² / g) and 3g of chloroprene rubber (CR) were placed in 100mL of anhydrous toluene and magnetically stirred at 300rpm for 12 hours at 25℃ to form a uniform second slurry.

[0062] S4. The obtained second slurry is applied to the surface of the first coating by a doctor blade coating method, with the doctor blade gap set to 90 μm and the coating speed at 2 m / min. The coated electrode is transferred to a vacuum oven and dried at 60°C and -0.095 MPa vacuum for 12 hours to remove the solvent. Subsequently, it is rolled at 150 MPa pressure to obtain the negative electrode.

[0063] In the resulting negative electrode sheet, the thickness of the first coating is 6 μm and the thickness of the second coating is 65 μm.

[0064] Example 2 The difference between this embodiment and Embodiment 1 is that the mass ratio of carbon black to PVDF in the first slurry is 9:1 (i.e., 90g carbon black + 10g PVDF), the doctor blade gap is set to 20μm, and the thickness of the first coating is 5μm.

[0065] Example 3 The difference between this embodiment and Embodiment 1 is that the mass ratio of Li6PS5Cl to silicon-carbon composite anode material in the second slurry is 20:80 (i.e., 20g Li6PS5Cl + 80g silicon-carbon material), and the rolling pressure is 100MPa.

[0066] Example 4 The difference between this embodiment and Embodiment 1 is that the mass ratio of carbon black to PVDF in the first slurry is 6:4 (i.e., 60g carbon black + 40g PVDF), and the thickness of the first coating is 3μm.

[0067] Example 5 The difference between this embodiment and Embodiment 1 is that the sulfide solid electrolyte in the second slurry is Li6PS5Br, the silicon content in the silicon-carbon anode composite material is 15wt%, and the specific surface area of ​​the porous carbon skeleton is 120 m² / g.

[0068] Example 6 This embodiment provides a negative electrode sheet for a sulfide all-solid-state battery, the preparation method of which includes the following steps: S1. Disperse 25g of conductive graphite, 25g of carbon nanotubes, 25g of graphene and 5g of polyacrylic acid in 80mL of DMF, and stir magnetically at 500rpm for 6 hours at room temperature to form a uniform first slurry.

[0069] S2. The obtained first slurry is applied to the surface of an 8μm thick electrolytic copper foil by a doctor blade coating method. The coated copper foil is transferred to a vacuum oven and dried at 80℃ and -0.095MPa vacuum for 4 hours to form a first coating layer (carbon coating layer) with a thickness of 4μm.

[0070] S3. In an argon glove box (O2<0.1 ppm, H2O<0.1 ppm), 10g of Li6PS5Cl powder (average particle size D50=2μm), 90g of silicon-carbon composite anode material (silicon content 20wt%, porous carbon skeleton specific surface area 200m² / g) and 1g of polyacrylic acid are placed in 100mL of isobutyl isobutyrate and magnetically stirred at 300rpm for 12 hours at 25℃ to form a uniform second slurry.

[0071] S4. The obtained second slurry is applied to the surface of the first coating by a doctor blade coating method. The coated electrode is transferred to a vacuum oven and dried at 60°C and -0.095MPa vacuum for 12 hours to remove the solvent. Subsequently, it is rolled at 100MPa pressure to obtain the negative electrode.

[0072] In the resulting negative electrode sheet, the thickness of the first coating is 3 μm and the thickness of the second coating is 60 μm.

[0073] Example 7 This embodiment provides a negative electrode sheet for a sulfide all-solid-state battery, the preparation method of which includes the following steps: S1. Disperse 45g carbon nanotubes, 50g graphene and 5g styrene-butadiene rubber in 100mL ethanol and stir magnetically at 500rpm for 6 hours at room temperature to form a uniform first slurry.

[0074] S2. The obtained first slurry is applied to the surface of an 8μm thick electrolytic copper foil using a doctor blade coating method. The coated copper foil is then transferred to a vacuum oven and dried at 80℃ and -0.095MPa vacuum for 4 hours to form a first coating layer (carbon coating layer) with a thickness of 5μm.

[0075] S3. In an argon glove box (O2<0.1 ppm, H2O<0.1 ppm), 40g of Li6PS5Cl powder (average particle size D50=2μm), 60g of silicon-carbon composite anode material (silicon content 20wt%, porous carbon skeleton specific surface area 80m² / g) and 5g of styrene-butadiene rubber were placed in 100mL of dichloromethane and magnetically stirred at 300rpm for 12 hours at 25℃ to form a uniform second slurry.

[0076] S4. The obtained second slurry is applied to the surface of the first coating by a doctor blade coating method. The coated electrode is transferred to a vacuum oven and dried at 60°C and -0.095MPa vacuum for 12 hours to remove the solvent. Subsequently, it is rolled at 50MPa pressure to obtain the negative electrode.

[0077] In the resulting negative electrode sheet, the thickness of the first coating is 5 μm and the thickness of the second coating is 70 μm.

[0078] Example 8 The only difference between this embodiment and Embodiment 1 is that the thickness of the first coating is 20 μm, and the coating thickness of the first slurry is adaptively adjusted.

[0079] Example 9 The only difference between this embodiment and Embodiment 1 is that the specific surface area of ​​the porous carbon framework is 200 m². 2 / g.

[0080] Comparative Example 1 The difference between this comparative example and Example 1 is that step S2 is omitted, that is, the second slurry is directly coated on the surface of the copper foil, and the first coating is not set.

[0081] Comparative Example 2 The difference between this comparative example and Example 1 is that no conductive carbon material is added to the first coating; it is only a pure PVDF polymer layer (ionically and electronically insulating).

[0082] Comparative Example 3 The difference between this comparative example and Example 1 is that the silicon-carbon composite anode material in the second slurry is replaced with pure silicon particles (without porous carbon skeleton).

[0083] Comparative Example 4 The difference between this comparative example and Example 1 is that no binder is added to the first coating.

[0084] Comparative Example 5 The difference between this comparative example and Example 1 is that the mass ratio of carbon black to polyvinylidene fluoride in the first coating is 45:55.

[0085] Comparative Example 6 The difference between this comparative example and Example 1 is that the thickness of the first coating is 0.3 μm, and the coating thickness of the first slurry is adaptively adjusted.

[0086] Comparative Example 7 The difference between this comparative example and Example 1 is that the thickness of the first coating is 25 μm, and the coating thickness of the first slurry is adaptively adjusted.

[0087] Comparative Example 8 The difference between this comparative example and Example 1 is that the mass ratio of the sulfide solid electrolyte and the silicon-carbon composite anode material in the second coating is 50:50.

[0088] Comparative Example 9 The difference between this comparative example and Example 1 is that the specific surface area of ​​the porous carbon framework is 220 m². 2 / g.

[0089] Comparative Example 10 The difference between this comparative example and Example 1 is that the solvent in the second slurry is replaced with DMSO.

[0090] Electrochemical performance testing The negative electrode obtained in the above examples and comparative examples was assembled with a sulfide solid electrolyte layer (Li6PS5Cl, 50 μm thick) and a positive electrode to form an all-solid-state battery, and its electrochemical performance was tested. Test conditions: 0.1C formation, 0.5C cycling, room temperature, stacking pressure 5 MPa.

[0091] Table 1 Electrical Performance Test Data

[0092] As can be seen from Table 1, the all-solid-state batteries assembled from the negative electrode sheets prepared in Examples 1-9 of this invention have an initial interfacial impedance of only 11-16 Ω·cm², which is much lower than that of the comparative examples. After 100 cycles, the interfacial impedance of the examples increased to 25-35 Ω·cm²; while the interfacial impedance of the comparative examples increased significantly compared to the examples, indicating that the present invention effectively suppressed the interfacial side reactions between the copper current collector and the sulfide electrolyte through the first coating.

[0093] In terms of cycle performance, the first-cycle coulombic efficiency of Examples 1-9 is 84.8%-88.7%, and the capacity retention rate after 100 cycles is 78.5%-83.8%, which is excellent.

[0094] In summary, this invention effectively improves the interface stability and cycle life of the negative electrode side of sulfide all-solid-state batteries by setting an electronically conductive / ionicly insulating carbon coating layer and optimizing the morphology of carbon materials in the composite negative electrode layer.

[0095] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode sheet for a sulfide all-solid-state battery, characterized in that, include: A current collector and a first coating and a second coating sequentially disposed on the surface of the current collector; The first coating is an electronically conductive and ionically insulating coating. The second coating comprises: a sulfide solid electrolyte and a silicon-carbon composite anode material.

2. The negative electrode of the sulfide all-solid-state battery according to claim 1, characterized in that, The electronic conductivity of the first coating is ≥10. -2 S / cm, ionic conductivity ≤10 -9 S / cm; And / or, the first coating comprises: a conductive carbon material and a binder in a mass ratio of 50~99:1~50.

3. The negative electrode of the sulfide all-solid-state battery according to claim 1, characterized in that, The thickness of the first coating is 1~20μm.

4. The negative electrode of the sulfide all-solid-state battery according to claim 2, characterized in that, The conductive carbon material includes at least one of carbon black, conductive graphite, carbon nanotubes, or graphene. And / or, the adhesive comprises at least one of polyvinylidene fluoride, polyacrylic acid, or styrene-butadiene rubber.

5. The negative electrode of the sulfide all-solid-state battery according to claim 1, characterized in that, In the second coating, the mass ratio of the sulfide solid electrolyte to the silicon-carbon composite anode material is 10~40:60~90.

6. The negative electrode of the sulfide all-solid-state battery according to claim 1, characterized in that, The silicon-carbon composite anode material includes: a porous carbon framework and silicon particles loaded in the porous carbon framework; And / or, the specific surface area of ​​the porous carbon framework is ≤200m². 2 / g.

7. The method for preparing the negative electrode sheet of the sulfide all-solid-state battery according to any one of claims 1 to 6, characterized in that, Includes the following steps: (a) After coating the first slurry onto the surface of the current collector, a first drying process is performed to form a first coating; (b) After applying the second slurry to the surface of the first coating, a second drying process and a roll pressing process are performed to form a second coating; The second slurry includes: a sulfide solid electrolyte and a silicon-carbon composite anode material.

8. The method for preparing the negative electrode sheet of the sulfide all-solid-state battery according to claim 7, characterized in that, The solvent for the second slurry includes: a non-polar organic solvent or a weakly polar organic solvent; And / or, the solvent of the second slurry has a dielectric constant ≤10 and does not contain hydroxyl or amino groups.

9. The method for preparing the negative electrode sheet of the sulfide all-solid-state battery according to claim 7, characterized in that, The pressure of the roller pressing process is 50~500MPa.

10. An all-solid-state battery, characterized in that, The negative electrode sheet of the sulfide all-solid-state battery as described in any one of claims 1 to 6.